Establishing an air-liquid interface exposure system for exposure of lung cells to gases. (21st March 2022) - Guénette, Josée; Breznan, Dalibor; Thomson, Errol M
Abstract: Objective: Growing interest in non-animal-based models has led to the development of devices to expose cells to airborne substances. Cells/tissues grown at the air-liquid interface (ALI) are more representative of lung cells/tissues in vivo compared to submerged cell cultures. Additionally, airborne exposures should allow for closer modeling of human lung toxicity. However, such exposures present technical challenges, including maintaining optimal cell health, and establishing consistent exposure monitoring and control. We aimed to establish a reliable system and procedures for cell exposures to gases at the ALI. Methods: We tested and adapted a horizontal-flow ALI-exposure system to verify and optimize temperature, humidity/condensation, and control of atmosphere delivery. We measured temperature and relative humidity (RH) throughout the system, including at the outlet (surrogate measures) and at the well, and evaluated viability of lung epithelial A549 cells under control conditions. Exposure stability, dosimetry, and toxicity were tested using ozone. Results: Temperatures measured directly above wells vs. outflow differed; using above-well temperature enabled determination of near-well RH. Under optimized conditions, the viability of A549 cells exposed to clean air (2 h) in the ALI system was unchanged from incubator-grown cells. In-well ozone levels, determined through reaction with potassium indigotrisulfonate, confirmed dosing. Cells exposed to 200 ppb ozone at the ALI presented reduced viability, while submerged cells did not. Conclusion: Our results emphasize the importance of monitoring near-well conditions rather than relying on surrogate measures. Rigorous assessment of ALI exposure conditions led to procedures for reproducible exposure of cells to gases.